2013
DOI: 10.1260/1708-5284.10.3.223
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of side emitting plastic optical fibers light intensity loss

Abstract: The main role of polymer optical fibers is to transmit light or optical signal to a specified spot. In the case of side emitting plastic optical fibers the light leaks out from their surface. This sidelight can be used for creation of optically active textile structures providing opportunities to highlight people and objects without the need for external exposure. Due to the transmission loss, the intensity of radiation emitted in any direction decays exponentially along the fiber axis with increasing distance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 9 publications
(13 reference statements)
0
11
0
Order By: Relevance
“…Internal illumination makes it possible to achieve a more homogeneous light distribution. To facilitate the design of illumination systems for batch reactors, Suh et al have developed a light distribution model that can predict the effects of using different numbers of radiators.…”
Section: Illumination Intensity In Bioreactorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Internal illumination makes it possible to achieve a more homogeneous light distribution. To facilitate the design of illumination systems for batch reactors, Suh et al have developed a light distribution model that can predict the effects of using different numbers of radiators.…”
Section: Illumination Intensity In Bioreactorsmentioning
confidence: 99%
“…However, the fibers must be treated to ensure that they will emit the guided light from their full length inside the reactor. Křemenáková et al has characterized laterally light emitting, polymeric optical fibers suitable for this purpose. It was shown that increasing the fiber diameter increases the illumination intensity and the attenuation coefficient but also increases the fibers’ rigidity.…”
Section: Illumination Intensity In Bioreactorsmentioning
confidence: 99%
“…Side emission can be achieved by launching light into the fibre below the critical angle, i.e. non‐guided light escapes after launching . An increased radial light emittance can also be achieved by applying macro‐bends and undulations within a textile manufacturing process .…”
Section: Introductionmentioning
confidence: 99%
“…In all cases, internal reflection should be avoided, either by changing the refractive indices of core and cladding or by changing the angle of incident light rays, e.g. by scattering or luminescence …”
Section: Introductionmentioning
confidence: 99%
“…This effect can be obtained by the increasing of cladding refractive index or by decreasing of core refractive index. It is possible to use multiple micro-bending of core or cladding; using particulates causes reflection into core/cladding or creation of geometric asymmetry in the core/cladding system [5].…”
Section: Introductionmentioning
confidence: 99%